Eutrophication alters bacterial co‐occurrence networks and increases the importance of chromophoric dissolved organic matter composition. Issue 6 (24th April 2021) - Zhou, Lei; Zhou, Yongqiang; Tang, Xiangming; Zhang, Yunlin; Zhu, Guangwei; Székely, Anna J; Jeppesen, Erik
Abstract: Eutrophication affects bacterial communities by fueling them with nutrients and carbon sources. While the influence of physicochemical conditions on bacterial communities is well studied, little is known about how dissolved organic matter (DOM) quality affects bacterial interspecific interactions and community composition with increasing eutrophication. Here, we examined the relative importance of physicochemical conditions and chromophoric DOM (CDOM) composition for bacterial community variation across trophic gradients using 109 samples data collected in 33 lakes of the Yangtze‐Huaihe River basin. We found a notable increase of bacterial abundance, elevated modularity of co‐occurrence networks, and decreased habitat niche breadths from mesotrophic sites to hyper‐eutrophic sites, suggesting changes in co‐occurrence patterns with eutrophication. Variation partitioning revealed that the proportion purely explained by CDOM composition was higher at the moderate‐ and hyper‐eutrophic sites than at the mesotrophic sites. Moreover, the module structures of the networks correlated significantly with CDOM composition at the eutrophic sites but not at the mesotrophic sites. The significant negative correlation between community‐level habitat niche breadths and the intensities of the protein‐like components at the moderate‐ and hyper‐eutrophic sites indicates a strong association between biolabile protein‐like compounds and habitat specialists in nutrient and substrate enriched lake systems. Our results suggest that consideration of DOM composition can strengthen the identification of links between environmental factors and bacterial community composition and interspecific interactions, especially under resource‐rich conditions.